Top 100 cited articles on Silver diamine fluoride-A bibliometric analysis - Zohra Jabin; Garima Jain; Manoj Jaiswal; V. Vishnu Priya (Elsevier, 2022)
Background: Identification of top cited articles aids in providing comprehensive and cumulative standardized quality work to research community. The present bibliometric study was aimed at identifying 100 top cited articles on Silver diamine fluoride, highlighting its landmark publications available in the current literature and aids in providing comprehensive and cumulative standardised quality work to research community. Methodology: Four major databases (Web of science, Pubmed, Scopus and Embase) were searched using search terms like 'silver fluoride' OR 'silver diamine fluoride' OR 'silverdiammine fluoride' OR 'diamine silver fluoride' OR 'diammine silver fluoride' OR silver ammonia fluoride AND dentistry. Selected publications were studied to tabulate information like journal, authors, year etc and contents of the publications were summarised. Variables such as journal name, first author, journal rank, citation count and average citations per year, authorship patterns, author's country of origin, most productive authors, journals and countries were identified. Additional outcome variables were SDF concentrations used, study designs adopted and SDF use like caries arrest/prevention/anti-hypersensitive agent and as an irrigant. Results: Among them maximum articles were clinical trials(n = 24) however systematic(n = 12), literature(n = 14) and narrative reviews(n = 12) had an equal share. The countries with the highest number of most-cited papers were China and USA. The most studied aspect was caries arrest. Journal of Dentistry and Journal of Dental Research had major publications among top cited papers. Conclusion: This particular review will prove to be a great source of information for research community worldwide and will aid in directing them towards relevant articles.